Spread and Distribution of Pollen Grains Collected by Honeybees Colonies in North Sinai with Reference to Pollen Chemical Composition. 2. Monthly Trapped Pollen of Combined Analysis - Abdal-Fattah, M. A.; EL-Bassioni, M. A.; Naser, E. Z. (2008)
Pollen offers a rich supply of easily nourishment to not only bees but also to many other insects. This experiment as regard to trapping of pollen grains were carried out in the Apiary and Laboratory of plant protection; Faculty of Environmental Agricultural Sciences; EI-Arish; Suez Canal University. EI-Arish province is situated at a distance of 365 Km from Cairo; its desert is located at the east of Egypt. Data and analysis of variance done on data of the two years of studying separately and combined; revealed that there was highly significant month's effect on the amount of pollen trapped. In 2003, the highest recorded amounts of pollen trapped were 58.9, 54.0 and 47.6 g during . April, July and August, respectively. Whilst, the highest amount of pollen trapped was recorded during August 2004 (107 g). However, the lowest amounts were recorded at the period from September till December in the both studied years.
Includes reference.
Summary in Arabic.
1
Keywords: Honeybee -- Feeding and feeds; Pollen; Honeybee -- Identification